Folia de Santos Reis : devoção e tradição popular da Comunidade Quilombola do São Félix, em Matrinchã-Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The purpose of this research is to make analyses and discussions about the Folia de Santos Reis through the concept of cultural heritage. The main objective is to show how the devotion and tradition of the Folia de Santos Reis of the remaining quilombola community São Félix, which is located in the region of Matrinchã - Goiás, works. At the same time, we intend to historicize the cultural asset of the research with the purpose of bringing the individuals of the quilombo and society closer to the historical reality of this immaterial celebration, leading them to reflect on this popular manifestation. Our work also presents a possibility of making visible and developing the rescue of our own identity. And among the specific objectives, we will seek to analyze the local cultural practices, in addition to understanding the beliefs, experiences and collective identity of the agents and producers of Santos Reis. We will also address the importance of the manifestation of the Folia in the cultural memory of the individuals of the quilombo and the city of Matrinchã, thus promoting discursive practices of appreciation of this cultural and religious tradition. In short, the results of the research indicate that, due to technological innovations, the Folia de Reis, over time, has undergone modifications and interventions in its customs and in the ways of expressing its beliefs. However, the agents of the festivities have been trying to keep the traditions of the folia alive. The final product of our investigation consists of a documentary video, which will be disseminated on social networks (Instagram, Facebook, WhatsApp, YouTube), school spaces and in the quilombola community, through which it can be used as a source of research, as well as can be taken as references to the possible implementation of actions and projects on the Folia de Santos Reis cultural heritage.
Keywords: Folia de Santos Reis; Identidade; Memória; Quilombo; Identity; Memory; CIENCIAS HUMANAS::HISTORIA